PERANCANGAN CORPORATE IDENTITY DISTRO BROTHER’S HOME PADANG - REZI AZHAR DARMADI, Dra. Zubaidah, M. Sn, San Ahdi, S.Sn., M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Distro Brother's Home is a distro which is located in the city of Padang. Distributions Brother's Home is located at Jalan By Pass Km 8 Kabun Kataping Padang. Inaugurated on October 8th, 2013 by Yonel Hasbi. The absence of Corporate Identity that can represent fully the vision and mission to shape the image to the presence of distributions Brother's Home is very influential in the competition, therefore the owners want to make Corporate Identity attractive and can represent fully the vision and mission to shape the image to the existence of distro Brother's Home, in addition to the corporate identity distributions Brother's Home will be made to have and charged meaning that represent Brother's Home in order to attract costumers to be able to visit the distributions Brother's Home, and can distinguish the distributions Brother's Home with other distributions in Padang city.Designing corporate identity as a major promotional media distributions Brother's Home, then through the media support, the necessary data analysis through SWOT. This method is needed to strengthen and refine the design.This design results in the form of corporate identity or the identity of the company which is expected to be a media campaign that is easily remembered by costumers, and can capture more customers and become the place of choice for visitors in the Padang city.Keyword : Distro Brother’s Home, Corporate Identiy, Media Campaign, SWOT.